International law as a profession - Aspremont, Jean d'; Gazzini, Tarcisio; Nollkaemper, André; Werner, W. G. (Wouter G.), 1966- (Cambridge : Cambridge University Press, 2017)
International law is not merely a set of rules or processes, but is a professional activity practised by a diversity of figures, including scholars, judges, counsel, teachers, legal advisers and activists. Individuals may, in different contexts, play more than one of these roles, and the interactions between them are illuminating of the nature of international law itself. This collection of innovative, multidisciplinary and self-reflective essays reveals a bilateral process whereby, on the one hand, the professionalisation of international law informs discourses about the law, and, on the other hand, discourses about the law inform the professionalisation of the discipline. Intended to promote a dialogue between practice and scholarship, this book is a must-read for all those engaged in the profession of international law.
Machine generated contents note: Introduction Jean d'Aspremont, Tarcisio Gazzini, Andre Nollkaemper and Wouter Werner; Part I. Thinking of International Law as a Professional Practice: 1. The professionalization of international law Jean d'Aspremont; 2. Between commitment and cynicism: outline for a theory of international law as practice Martti Koskenniemi; 3. The (academic) profession of international law and the commitment to legal autonomy Alexandra Bohm and Richard Collins; 4. Scientific reason and the discipline of international law Anne Orford; Part II. The Practice of International Law and its Theories: 5. Realizing Utopia as a scholarly endeavour Anne Peters; 6. The activist academic in international legal scholarship Gleider Hernandez; 7. How NAIL works: the production of heterodoxy in international law Akbar Rasulov; 8. International legal research and the quest for immanent moral order Jochen von Bernstorff; 9. The turn to history within international legal scholarship John Haskell; 10. International legal theory qua practice of international law Samantha Besson; Part III. The Practice of International Law and its Professional Capacities: 11. International law as practice: moving past the anxieties of interdisciplinarity Tanja Aalberts and Ingo Venzke; 12. Towards a political sociology of international justice(s) Sara Dezalay and Yves Dezalay; 13. The international law bar: essence before existence? James Crawford; 14. Consigliere or conscience: the legal adviser's dilemma Matthew Windsor; 15. International law as expertise: exploring pluralism and the anxiety of certainty as professional experiences Rene Uruena; 16. Teachers of international law Pierre d'Argent; Concluding remarks: the Praxis of international law Wouter Werner.
Title from publisher's bibliographic system (viewed on 21 Apr 2017).
Keywords: International law -- Study and teaching; Practice of law